An Overview of the Environmental Applicability of Vermicompost: From Wastewater Treatment to the Development of Sensitive Analytical Methods. (21st January 2014) - Pereira, Madson de Godoi; Cardoso de Souza Neta, Lourdes; Fontes, Maurício Paulo Ferreira; Souza, Adriana Nascimento; Carvalho Matos, Thaionara; de Lima Sachdev, Raquel; dos Santos, Arnaud Victor; Oliveira da Guarda Souza, Marluce; de Andrade, Marta Valéria Almeida Santana; Marinho Maciel Paulo, Gabriela; Ribeiro, Joselito Nardy; Verónica Flores Nardy Ribeiro, Araceli
Abstract : The use of vermicompost (humified material) for treating wastewaters, remediating polluted soils, improving agricultural productivity, protecting crop production, and developing sensitive analytical methods is reviewed here, covering the past 17 years. The main advantages of vermicompost, considering all applications covered in this paper, comprise (i) easy acquisition, (ii) low costs, (iii) structural, chemical, and biological characteristics responsible for exceptional adsorptive capacities as well as pollutant degradation, and (iv) the promotion of biocontrol. Specifically, for wastewater decontamination, a considerable number of works have verified the adsorption of toxic metals, but the application of vermicompost is still scarce for the retention of organic compounds. Problems related to the final disposal of enriched vermicompost (after treatment steps) are often found, in spite of some successful destinations such as organic fertilizer. For decontaminating soils, the use of vermicompost is quite scarce, mainly for inorganic pollutants. In agricultural productivity and biocontrol, vermicompost imparts remarkable benefits regarding soil aggregation, plant nutrition, and the development of beneficial microorganisms against phytopathogens. Finally, the use of vermicompost in sensitive analytical methods for quantifying toxic metals is the newest application of this adsorbent.